2018
DOI: 10.3389/fmicb.2018.01913
|View full text |Cite
|
Sign up to set email alerts
|

Broad Bean (Vicia faba L.) Induces Intestinal Inflammation in Grass Carp (Ctenopharyngodon idellus C. et V) by Increasing Relative Abundances of Intestinal Gram-Negative and Flagellated Bacteria

Abstract: Constant consumption of broad bean (Vicia faba L.) induces intestinal inflammation and reduces growth rate in grass carp (Ctenopharyngodon idellus C. et V). However, the mechanisms underlying these effects are unclear. In mammalian models of inflammatory bowel disease (IBD), endotoxin and flagellin cause intestinal inflammation through upregulation of tumor necrosis factor (TNF)-α expression. We therefore speculated that broad bean consumption alters intestinal microbiota composition, thereby increasing the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 53 publications
(61 reference statements)
0
16
0
Order By: Relevance
“…Interestingly, faba bean has been suggested to cause intestinal damage and induce inflammation in grass carps (Li et al, 2018), and wounds have been reported to attract fat cells to drive repair and prevent infection (Franz et al, 2018). However, further studies are needed to determine whether intestinal damage or inflammation can induce fat accumulation in peri-intestinal tissues of fish.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, faba bean has been suggested to cause intestinal damage and induce inflammation in grass carps (Li et al, 2018), and wounds have been reported to attract fat cells to drive repair and prevent infection (Franz et al, 2018). However, further studies are needed to determine whether intestinal damage or inflammation can induce fat accumulation in peri-intestinal tissues of fish.…”
Section: Discussionmentioning
confidence: 99%
“…These antinutritional factors reduced the activity of digestive enzymes (Li, Leng, Li, Liu, et al, ; Zheng et al, ) and thus negatively affected the digestion and absorption of nutrients. Moreover, broad bean was reported to induce intestinal inflammation in grass carp (Li et al, ). In the present trial, grass carp fed SBB were found to consume the diet slowly, and some fish even vomited after eating during the feeding period.…”
Section: Discussionmentioning
confidence: 99%
“…The values were calculated through the R indicspecies package. Screened genera were verified using the standard non-parametric Kruskal–Wallis test through R with the ggpubr package according to a previous report (Li et al, 2018). The Kruskal–Wallis test was also used to detect the statistical significance of alpha-diversity indices among patients with different stages of HCC and healthy controls.…”
Section: Methodsmentioning
confidence: 99%